Analisis Karakter Gotong Royong Sebagai Penguatan Jati Diri Bangsa Pada Animasi Adit Dan Sopo Jarwo - Kintan Vindria Salsabila; Tita Mulyati; Yayang Furi Furnamasari (International Forum of Researchers and Lecturers, 2023)
This research aims to identify the values of mutual cooperation character found in the Adit and Sopo Jarwo animation as one of the media to be used in strengthening the national identity of elementary school students. The method used in this research is qualitative with content analysis method, and data collection techniques include literature study, documentation, and data analysis. Based on the results of the research conducted, it was found that in the Adit and Sopo Jarwo animated film, there are 7 values of mutual cooperation character, which are helping each other, appreciating teamwork, solidarity, commitment to collective decisions, empathy, anti-violence, and a voluntary attitude. These values of mutual cooperation character appear in 11 episodes of the Adit and Sopo Jarwo animation, namely in the episodes of the father's lost wallet, the father's wallet is still lost, Jarwo's theft, Adit wins, the confusing umbrella motorcycle taxi, Adit's flu, Jarwo's sadness, getting caught up in the antenna service, kite competition making everyone fly, Jarwo's surprise, Adel's whereabouts, patrol duties like courage tests, and visiting siblings making everyone feel honored. Furthermore, the Adit and Sopo Jarwo animation can be used as a learning tool in strengthening the national identity because this animation contains scenes that are in line with the development of mutual cooperation character as a way to strengthen the national identity.